Synthesis and Characterisation of Various Diester and Triester Adducts of TiCl4. Issue 22 (30th June 2015) - Blackburn, Ben J.; Crane, Jared H.; Knapp, Caroline E.; Marchand, Peter; Pugh, David; Parkin, Ivan P.; Carmalt, Claire J.
Abstract: Titanium(IV) chloride and the triester glycerol tribenzoate (gtb) were reacted under moisture‐free conditions in order to investigate the use of triester‐containing oils in the purification of TiCl4 in industrial processes. This resulted in the isolation of a chloro‐bridged dimeric complex containing four titanium centres [{(TiCl4 )2 (gtb)}2 ] (1 ). Further novel coordination compounds of TiCl4 and the diesters; diisopropyl malonate, dibenzyl malonate and diethyl succinate were synthesised by direct reaction under moisture‐free conditions, yielding [TiCl4 {CH2 (COO i Pr)2 }] (2 ), [TiCl4 {CH2 (COOCH2 Ph)2 }] (3 ) and [TiCl4 {C2 H4 (COOEt)2 }] (4 ) respectively. The structures of compounds1 –4 were determined by single‐crystal X‐ray diffraction. All structures assumed an octahedral geometry consisting of the titanium bound to four chloride ligands and the diester molecule acting as a bidentate ligand, through its two carbonyl oxygen atoms. Exposure of the isopropyl malonate reaction to trace amounts of water during synthesis resulted in the formation of an oxo‐bridged dimeric structure [Ti2 (μ‐O)Cl3 {CH2 (COO i Pr)2 }2 ] (2b ), the structure of which was also obtained via single‐crystal X‐ray diffraction. Abstract : The synthesis of novel titanium complexes with triesters and diesters was achieved using Schlenk techniques for the purpose of ellucidating the previously unknown mechanisms at play during the industrially used Chloride Process.